EKSTRAK DAUN JAMBU METE KONSENTRASI 10% YANG DIKUMURKAN DAPAT MENGHAMBAT PERTUMBUHAN STREPTOCOCCUS MUTANS SALIVA: GARGLING 10% CASHEW LEAVES EXTRACT INHIBITS THE GROWTH OF STREPTOCOCCUS MUTANS IN SALIVA - Rizki Fadlilah; Juni Handajani; Tetiana Haniastuti (Dentika: Dental Journal, 2010)
Dental caries is the most dominant tooth disease that is caused predominantly by Streptococcus mutans. S. mutans is Gram positive facultative anaerobic bacteria and can be found in saliva. Cashew leaves extract (Anacardium occidentale L.) contains of antibacterial substance namely flavonoid, tanin and triterpenoid. The objective of this study was to examine the effect of gargling with 10% cashew leaves extract in S. mutans growth inhibition in saliva. In this study, 15 subjects were divided randomly into 3 groups (treatment, positive and negative control). Each group consists of 5 persons. Treatment group gargled with 10% cashew leaves extract, while positive control group gargled with 0.2% Chlorhexidine gluconate and negative control group gargled with aquades for 5 consecutive days in the morning and night after they brushed their teeth. S. mutans in saliva was cultivated anaerobicly on Trypticase soy extract of Yeast Sucrose Bacitracin agar for 24 hours. The results showed that 10% cashew leaves extract inhibited S. mutans growth in saliva (p<0.05). There was no significant difference between the number of S. mutans in samples who gargled with 10% cashew leaves extract and 0.2% Chlorhexidine gluconate (p>0.05). In conclusion, gargling with 10% cashew leaves extract may inhibit the growth of S. mutans in saliva. Ten percent cashew leaves extract may has similar potency as 0.2 % Chlorhexidine gluconate in S. mutans growth inhibition.